Reliability of clinical judgment for evaluation of informed consent in mental health settings and the validation of the Evaluation of Informed Consent to Treatment (EICT) scale - Di Fazio, Nicola; Morena, Donato; Piras, Federica; Piras, Fabrizio; Banaj, Nerisa; Delogu, Giuseppe; Damato, Felice; Frati, Paola; Fineschi, Vittorio; Ferracuti, Stefano; Sani, Gabriele; Dacquino, Claudia (Frontiers in Psychology, 2024)
The competence assessment to give informed consent in the legal and healthcare settings is often performed merely through clinical judgment. In the present pilot study, we evaluated the reliability of clinical judgment in the mental health field, with a focus on assessing the general competence of outpatients with schizophrenia. Moreover, we tested a new scale ("Evaluation of Informed Consent to Treatment" -"EICT" Scale) suitable as a standardized assessment tool. The scale assesses four dimensions of competence, Understanding, Evaluating. Reasoning and Expressing a choice. Thirty-four outpatients with schizophrenia were evaluated for their competence to consent by five referring clinicians with different backgrounds (psychiatrist, forensic psychiatrist, geriatrician, anesthetist, and medico-legal doctor). Correlation analyses were conducted between the scores obtained by the clinicians on a modified version of the Global Assessment of Functioning scale (GAF) designed specifically to subjectively assess functioning in each of the four competence dimensions. Moreover, two validated competence scales (Mac-CAT-T, SICIATRI-R), and a neuropsychological battery were administered along with scales for evaluating neuropsychiatric symptoms severity and side effects of medication. Clinical judgments of the individual specialists showed great inter-rater variability. Likewise, only weak/non-significant correlations were found between the EICT subscales and the respective clinicians-rated GAF scales. Conversely, solid correlations were found between the EICT and MacCAT-T subscales. Healthy controls performed better in the ability to give informed consent to treatment, as measured by the three scales (i.e., EICT, MacCAT-T, and SICIATRI-R), and neuropsychological test performance. In the comparisons between patients able or not able to give informed consent to treatment, significant differences emerged for the Phonemic verbal fluency task (p=0.038), Verbal judgments (p=0.048), MacCAT-T subscales, and SICIATRI-R total score. Moreover, EICT exhibited excellent internal consistency while the Item Analysis was excellent for all items of all subscales (alphas ranging from 0.86 to 0.98). In conclusion, our findings highlighted that the assessment of competence exclusively through clinical judgment is not fully reliable and needs the support of standardized tools. The EICT scale could therefore be useful in assessing general competence to consent both in healthcare and legal contexts